COVID-19 induced whatsapp platform for efal learners in a multilingual context - Zano, Kufakunesu; Charamba, Erasmos (Penerbit Universiti Kebangsaan Malaysia, 2021)
The fame of the WhatsApp Group in the academic circle has raised the interest of researchers in investigating its potential benefit in the teaching and learning of English First Additional Language (EFAL) in a multilingual setting. This study seeks to investigate the opinions of the EFAL learners on the use of the WhatsApp platform as a learning tool in an EFAL context outside the classroom during the Covid-19-induced school holiday. This study was designed as a qualitative research project where only 30 EFAL learners in Grade 12 were used as participants. A focus group interview was used to collect data from the participants. In 6 groups of 5 each, they shared their opinions on the importance of WhatsApp as an online resource in an EFAL context. The results of the study revealed that WhatsApp is for just about anything therefore its presence and influence become inevitable in an academic context. The ‘contaminating effect’ of the WhatsApp platform on EFAL learners’ writing, reading and speaking is now commonplace. However, EFAL teachers need to accept that texts of technologies are mutating into complex hybrid systems that will inevitably and justifiably make new demands on reading, speaking and writing, viewing, social exchange and communication. The study also highlights the socio-economic and contextual factors that complicate the relationships between EFAL teaching and technology. It becomes imperative for the relevant stakeholders to reconsider teacher professional development, which should not be a one-size-fits-all approach because EFAL teachers operate in different teaching and learning contexts.